Delivery of Light to Buildings - Žák, Petr; Habel, Jiří; Panská, Zuzana (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
Current method of design and evaluation of interior lighting in buildings is pulverized to the solution of individual spaces. Separately is evaluated energy consumption for lighting in the building. In this situation is very difficult to optimize the lighting systems. The relationship between the needs for lighting and overall energy consumption for lighting is not obvious. Clearer connection can be found in the simplified view of the whole issue. The required lighting levels and thus energy consumption in buildings are affected by three basic aspects. The first aspect is the usage of the building, i.e. what types of visual tasks in a building are exercised. The basic parameter for quantitative evaluation of visual requirements in today's practice is the illuminance E (Ix). The second aspect is the size of the building, thus the dimensions of spaces in which the visual tasks are performed. In this case the basic parameter is the illuminated area A (m2). The last aspect is the time during which the visual tasks are performed, expressed by operating time T (h). In this view the issue of the interior lighting in buildings can be converted to the delivery of luminous flux Φ (lm) or quantity of light QV (lm.h / year). Such expression is conceptually close to requirements for the supply of other media to the buildings, such as heat, air, water etc. The above considerations set the desired amount of luminous flux, respectively quantity of light. The next step is to set lighting quality parameters such as a minimum proportion of daylight, uniformity, limitation of the glare, the colour properties of light. In the last step, the optimal technical solution is found by selecting the type of lighting systems, light sources and luminaires, which meets both quantitative and qualitative requirements of lighting. Such approaches allow the creation of ideas about lighting needs in the initial stages of project and convert them to specific technical solutions.
Dodávka světla do budov
Keywords: Daylighting; artificial lighting; energy consumption; luminous flux; quantity of light.